It's easy, believe me!

Given a a and b b are two integers that satisfy

lcm ( x 2 + a x 2 , x 2 + 5 x + b ) = x 3 + 4 x 2 + x 6 \large \text{lcm} \left(x^2 + ax - 2, x^2 + 5x + b\right) = x^3 + 4x^2 + x - 6

Calculate a + b a + b .

Notation: lcm ( ) \text{lcm}(\cdots) denotes the lowest common multiple .


This is part of the set: It's easy, believe me!


The answer is 7.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Marco Brezzi
Aug 11, 2017

Firstly we factor the l c m lcm

x 3 + 4 x 2 + x 6 = ( x 1 ) ( x + 2 ) ( x + 3 ) x^3+4x^2+x-6=(x-1)(x+2)(x+3)

So x 2 + a 2 x^2+a-2 and x 2 + 5 x + b x^2+5x+b are each the product of 2 2 of the 3 3 factors of the l c m lcm

In the first polynomial the products of the roots is 2 -2 , so we must have

x 2 + a x 2 = ( x 1 ) ( x + 2 ) = x 2 + x 2 a = 1 x^2+ax-2=(x-1)(x+2)=x^2+x-2 \Longrightarrow \mathbin{\color{#D61F06}a=1}

In the second one the sum of the roots is 5 -5 , so we must have

x 2 + 5 x + b = ( x + 2 ) ( x + 3 ) = x 2 + 5 x + 6 b = 6 x^2+5x+b=(x+2)(x+3)=x^2+5x+6 \Longrightarrow \mathbin{\color{#3D99F6}b=6}

a + b = 1 + 6 = 7 \Longrightarrow \mathbin{\color{#D61F06}a}+\mathbin{\color{#3D99F6}b}=\mathbin{\color{#D61F06}1}+\mathbin{\color{#3D99F6}6}=\boxed{7}

Same solution.

Niranjan Khanderia - 2 years, 7 months ago
Saksham Jain
Nov 11, 2017

factorize lcm by factor thoeorem (x-1)(x+2)(x+3) therefore 1 st is (x-1)(x+2)=x^2+x-2 2nd is (x+2)(x+3)=x^2+5x+6 a+b is 7

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...